2014
DOI: 10.1111/jace.13034
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Abnormal Grain Growths in BaTiO3 Fibers

Abstract: The grain growth mechanisms along the BaTiO3 fibers were studied between 1150°C and 1250°C. The normal grain growth always reached a stagnant stage after certain heat‐treatment duration caused by the surface pinning effect. However, the abnormal grain growth (AGG) was not pinned by such surface effect, and can grow continuously. The confined normal grain (or matrix grain) size provides the driving force for AGG. The fiber diameter has an important influence on the grain growth behaviors. Submicrometer fibers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…, the activation energy of grain growth of tetragonal barium titanate was calculated to be 2.641 ± .377 eV/(atom K ). This fits in to a trend previously observed in barium titanate nanofibers by Peng et al where the activation energy of grain growth was found to decrease with decreasing fiber diameter …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…, the activation energy of grain growth of tetragonal barium titanate was calculated to be 2.641 ± .377 eV/(atom K ). This fits in to a trend previously observed in barium titanate nanofibers by Peng et al where the activation energy of grain growth was found to decrease with decreasing fiber diameter …”
Section: Resultssupporting
confidence: 91%
“…This fits in to a trend previously observed in barium titanate nanofibers by Peng et al where the activation energy of grain growth was found to decrease with decreasing fiber diameter. 44 Lastly, the piezoelectric properties of the electrospun barium titanate nanofibers were determined using PFM. Figure 8(a) shows the butterfly loop, with corresponding phase plot Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of grain growth, the correlation between the boundary faceting and the boundary migration, as well as grain growth behavior, has been much more carefully studied . As in the case of densification, Figure indicates the presence of a critical driving force for grain growth in a sample with faceted boundaries.…”
Section: Fundamentals Of Sintering and Microstructure Evolutionmentioning
confidence: 99%
“…[1][2][3][4][5] The first record of an LLP material, which was found in nature, was during the Song Dynasty of China (11 th century A.D.). 6 In 1602, Italian Vincenzo Casciarolo discovered the famous Bolognian stone, which could emit blue-violet light for a few minutes in darkness.…”
Section: Introductionmentioning
confidence: 99%